2020
DOI: 10.1002/ana.25793
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐Early Blood Pressure Reduction Attenuates Hematoma Growth and Improves Outcome in Intracerebral Hemorrhage

Abstract: Objective The aim was to investigate whether intensive blood pressure treatment is associated with less hematoma growth and better outcome in intracerebral hemorrhage (ICH) patients who received intravenous nicardipine treatment ≤2 hours after onset of symptoms. Methods A post‐hoc exploratory analysis of the Antihypertensive Treatment of Acute Cerebral Hemorrhage 2 (ATACH‐2) trial was performed. This was a multicenter, international, open‐label, randomized clinical trial, in which patients with primary ICH wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(85 citation statements)
references
References 33 publications
(87 reference statements)
0
84
0
1
Order By: Relevance
“…The mechanisms of the effect are unclear. There are a few possibilities: (1) dehydration is known to increase blood viscosity and to decrease blood pressure and cerebral perfusion (4,15), leading to reduced hematoma growth and good in-hospital outcome (16,17). (2) Dehydration-related hypovolemia and hypernatremia may increase intravascular osmolality and reduce perihematomal edema and intracranial pressure (18)(19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of the effect are unclear. There are a few possibilities: (1) dehydration is known to increase blood viscosity and to decrease blood pressure and cerebral perfusion (4,15), leading to reduced hematoma growth and good in-hospital outcome (16,17). (2) Dehydration-related hypovolemia and hypernatremia may increase intravascular osmolality and reduce perihematomal edema and intracranial pressure (18)(19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, many ICH patients arrive at the emergency department within several hours due to the rapid symptom onset. In addition, a recent secondary analysis of the ATACH2 trial results suggested that ultra-early blood pressure reduction was associated with a reduced rate of hematoma growth and improved functional outcomes in ICH patients ( 33 ). Therefore, outcome prediction within a few hours after ICH onset is important for clinicians to delineate the potential benefits of aggressive care.…”
Section: Discussionmentioning
confidence: 99%
“…Using a comparator of all direct and metropolitan secondary transfer patients to the largest EVT center in Victoria (Royal Melbourne Hospital), patients receiving facilitated thrombectomy via the Melbourne MSU did so a median of 51 min (95%CI: 30-72) faster. On further analysis, cases that bypassed of the local non-EVT hospital received the most time saving of 71 min (95%CI: 46-96), whereas the equivalent time saving if the patient was located closest to a comprehensive center was 6 min (95%CI: [19][20][21][22][23][24][25][26][27][28][29][30][31]. This suggests that a large proportion of the time savings are due to improved triage and avoidance of secondary transfers.…”
Section: Benefits For Endovascular Thrombectomymentioning
confidence: 99%
“…Although effective treatments are much more limited for parenchymal intracerebral hemorrhage, a posthoc analysis of a major trial of aggressive blood pressure management in intracerebral hemorrhage demonstrated improved outcomes if anti-hypertensive therapy is initiated within 2 h of symptom onset [31] . In the first 365 days, 42% of MSU hemorrhage patients required acute intravenous anti-hypertensive therapy, which would be delayed if patients received standard ambulance transport.…”
Section: Benefits For Hemorrhagic Strokementioning
confidence: 99%